Anesthetic and surgical management of tracheostomy in a patient with COVID-19. Issue 3 (June 2020) - Hiramatsu, Mariko; Nishio, Naoki; Ozaki, Masayuki; Shindo, Yuichiro; Suzuki, Katsunao; Yamamoto, Takanori; Fujimoto, Yasushi; Sone, Michihiko
Abstract: Objective: The ongoing pandemic coronavirus disease-2019 (COVID-19) infection causes severe respiratory dysfunction and has become an emergent issue for worldwide healthcare. Since COVID-19 spreads through contact and droplet infection routes, careful attention to infection control and surgical management is important to prevent cross-contamination of patients and medical staff. Tracheostomy is an effective method to treat severe respiratory dysfunction with prolonged respiratory management and should be performed as a high-risk procedure Method: The anesthetic and surgical considerations in this case involved difficult goals of the patient safety and the management of infection among health care workers. Our surgical procedure was developed based on the previous experiences of severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV). Results: We described the management procedures for tracheostomy in a patient with COVID-19, including the anesthesia preparation, surgical procedures, required medical supplies (a N95 mask or powered air purifying respirator, goggles, face shield, cap, double gloves, and a water-resistant disposable gown), and appropriate consultation with an infection prevention team. Conclusion: Appropriate contact, airborne precautions, and sufficient use of muscle relaxants are essential for performing tracheostomy in a patient with COVID-19.